Pencegahan Tindak Pidana Pencucian Uang Oleh Kegiatan Usaha Penukaran Valuta Asing Bukan Bank Di Indonesia - Agnestya Putri Rizon; Shenti Agustini (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
Money laundering is an attempt to hide or disguise the origin of money/funds or assets resulting from criminal acts through various financial transactions so that the money or assets appear as if they came from legal/legal activities. Data obtained based on the Anti-Money Laundering and Terrorism Statistical Bulletin by the Center for Financial Transactions and Analysis Services in June 2019, there were 459,951 Suspicious Financial Transaction Reports during the period January 2003 to June 2019 received by PPATK. Types of research used in the study This is a normative juridical research that is used to review the legislation. It is useful for academic purposes which is used for academic purposes and can be used to compose academic works. With the new provisions, the implementation of regulations for KUPVA BB operators and Payment System Service Providers (PJSP) has been integrated. The new regulations have also been harmonized with the government's efforts to combat money laundering and terrorism financing, as well as recommendations and guidelines provided by the international Financial Action Task Force on Money Laundering (FATF). The obligation to report Money Changers and early monitoring by PPATK as an effort to combat money laundering is a preventive measure in preventing money laundering crimes. The new regulations have also been harmonized with the government's efforts to combat money laundering and terrorism financing, as well as recommendations and guidelines provided by the international Financial Action Task Force on Money Laundering (FATF). The obligation to report Money Changers and early monitoring by PPATK as an effort to combat money laundering is a preventive measure in preventing money laundering crimes. The new regulations have also been harmonized with the government's efforts to combat money laundering and terrorism financing, as well as recommendations and guidelines provided by the international Financial Action Task Force on Money Laundering (FATF). The obligation to report Money Changers and early monitoring by PPATK as an effort to combat money laundering is a preventive measure in preventing money laundering crimes.